57.7k views
1 vote
Y^2 − 20x − 6y − 51 = 0

User Nogwater
by
6.7k points

1 Answer

7 votes

answer:

Simplifying Y2 + -20X + -6y + -51 = 0

Reorder the terms: -51 + -20X + Y2 + -6y = 0

Solving -51 + -20X + Y2 + -6y = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '51' to each side of the equation. -51 + -20X + Y2 + 51 + -6y = 0 + 51

Reorder the terms: -51 + 51 + -20X + Y2 + -6y = 0 + 51 Combine like terms: -51 + 51 = 0 0 + -20X + Y2 + -6y = 0 + 51 -20X + Y2 + -6y = 0 + 51

Combine like terms: 0 + 51 = 51 -20X + Y2 + -6y = 51

Add '-1Y2' to each side of the equation. -20X + Y2 + -1Y2 + -6y = 51 + -1Y2

Combine like terms: Y2 + -1Y2 = 0 -20X + 0 + -6y = 51 + -1Y2 -20X + -6y = 51 + -1Y2 Add '6y' to each side of the equation. -20X + -6y + 6y = 51 + -1Y2 + 6y Combine like terms: -6y + 6y = 0 -20X + 0 = 51 + -1Y2 + 6y -20X = 51 + -1Y2 + 6y Divide each side by '-20'. X = -2.55 + 0.05Y2 + -0.3y Simplifying X = -2.55 + 0.05Y2 + -0.3y

User Marvo
by
5.9k points